KUALITAS SIFAT KIMIA POC LIMBAH BUAH YANG DIBERI BAHAN-BAHAN PENINGKAT HARA N, P, DAN K - Lena Walunguru; Marsema Marselin Kaka Mone (Politeknik Pertanian Negeri Kupang, 2019)
This study aims to determine the chemical properties and escalation levels of macro (N, P, and K) and micro nutrients of Liquid Organic Fertilizer (LOF) made from papaya, apple, pineapple, and saba banana peels which were given the addition of several organic nutrients to enhance N, P, and K. The research design was an experiment in the form of a simple data analysis based on the average value of observations. Liquid organic fertilizer of fruit waste (papaya, apples, pineapples, and saba banana) added with several organic substances enhancing nutrients N, P, and K have better chemical properties where the C-organic content is 17.55% higher 1.2% compared to LOF fruit waste; pH value is 4.18 compared to LOF of fruit waste which is 3.6; macro nutrients namely N levels of 1.24% more 0.06%, P levels of 321.7 ppm 36.8 ppm more, K levels of 139.3 ppm 10.2 ppm more, Ca levels of 294.1 ppm 117.4 ppm more, and Mg levels of 176.7 ppm more 0.12 ppm; and micronutrients that are increased around 0.02-1.54 ppm, where Fe nutrient levels increased by 1.54 ppm, Cu by 0.05 ppm, Zn by 0.62 ppm, and Mn by 0.02 ppm.